2015
DOI: 10.1002/anie.201500620
|View full text |Cite
|
Sign up to set email alerts
|

Facile Hydrolysis and Alcoholysis of Palladium Acetate

Abstract: Palladium(II) acetate is readily converted into [Pd3 (μ(2) -OH)(OAc)5 ] (1) in the presence of water in a range of organic solvents and is also slowly converted in the solid state. Complex 1 can also be formed in nominally anhydrous solvents. Similarly, the analogous alkoxide complexes [Pd3 (μ(2) -OR)(OAc)5 ] (3) are easily formed in solutions of palladium(II) acetate containing a range of alcohols. An examination of a representative Wacker-type oxidation shows that the Pd-OH complex 1 and a related Pd-oxo com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 20 publications
3
25
0
1
Order By: Relevance
“…Compound 1 was readily obtained from 1,3-diisopropylimidazolium chloride [37] by reaction with elemental sulfur in MeOH in the presence of K 2 CO 3 [42]. Recrystallization from benzene allows effective removal of elemental sulfur and yields 1 as a colorless, crystalline solid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 1 was readily obtained from 1,3-diisopropylimidazolium chloride [37] by reaction with elemental sulfur in MeOH in the presence of K 2 CO 3 [42]. Recrystallization from benzene allows effective removal of elemental sulfur and yields 1 as a colorless, crystalline solid.…”
Section: Resultsmentioning
confidence: 99%
“…All experiments involving metal complexes were carried out using standard Schlenk techniques under an argon atmosphere, in particular to avoid hydrolysis of palladium(II) acetate [37]. Solvents were dried using standard procedures and distilled prior to use, or passed through activated alumina and subsequently purged with argon.…”
Section: Methodsmentioning
confidence: 99%
“…64 The degradation of Pd(OAc) 2 and Pd 2 (dba) 3 has been utilised by Gómez et al to produce PdNPs of ca. 72 Their work makes clear that in any catalytic process utilising Pd(OAc) 2 , intermediates such as those shown in Scheme 6 should be considered as relevant species. This protocol was shown to be effective when catalysed by preformed PVP-supported PdNPs of around 1-2 nm.…”
Section: Studies On Suzuki-miyaura Cross-coupling Reactionsmentioning
confidence: 99%
“…Although 1 is believed to be an air‐ and moisture‐stable compound, it has been shown to react readily with trace amounts of water ( 4 ) and certain alcohols ( 5 ) to generate new species in solution which adds further complexity to its characterization and activity studies. In addition, Bedford and co‐workers recently demonstrated that 1 will slowly convert to 4 (34 %) when left exposed to air for eight days, highlighting the importance of storage conditions due to its water sensitivity in the solid state …”
Section: Introductionmentioning
confidence: 99%